Antioxidant potential of hydro-methanolic extract of seed of Caesalpinia bonduc: An in vitro study - Kishalay Jana; Kausik Chatterjee; Kazi Monjur Ali; Abhinandan Ghosh; Tushar Kanti Bera; Debidas Ghosh (Wolters Kluwer Medknow Publications, 2011)
It is well known that the over production of reactive oxygen species is harmful for living organisms and it damages major cellular constituents such as DNA, protein, and lipid. At present, searching of new plant sources having free radical scavenging activity is an important field of research in phytomedicine as natural products are safe and relatively low cost. In this respect, attention has been focused to evaluate the antioxidant potential of hydro-methanolic extract of seed of Caesalpinia bonduc (Caesalpenacae) using different in vitro models. To evaluate the antioxidant activity, extract was examined on 2, 2-diphenyl-1-picrylhydrazyl radical scavenging effect, scavenging of hydrogen peroxide, hydroxyl radical scavenging potential, and anti-lipid peroxidation activity by biochemical methods. Total phenol and flavonoids contents in the said extract were measured biochemically as per standard methods. Results were compared with butylated hydroxyl toluene and α-tocopherol. Results indicated that hydro-methanolic extract has strong scavenging activity on 2, 2-diphenyl-1-picrylhydrazyl radical with IC 50 value 157.4 μg/ml, hydroxyl radical with IC 50 value 61.9 μg/ml and hydrogen peroxide with IC 50 value 64.32 μg/ml. Hydro-methanolic extract also showed notable inhibition in lipid peroxidation having IC 50 value 58.87 μg/ml. Phytochemical study focused that the extract is rich in phenolic compounds (24.66 mg gallic acid equivalent/g dried extract) and flavonoids (136.65 mg quercetin equivalent/g dried extract). Findings of the experiment indicated that the hydro-methanolic extract of seed of Caesalpinia bonduc is a source of natural antioxidants.